Valvulo-Arterial Impedance and Dimensionless Index for Risk Stratifying Patients With Severe Aortic Stenosis - Mantha, Yogamaya; Futami, Shutaro; Moriyama, Shohei; Hieda, Michinari (Frontiers in Cardiovascular Medicine, 2021)
The hemodynamic effects of aortic stenosis (AS) consist of increased left ventricular (LV) afterload, reduced myocardial compliance, and increased myocardial workload. The LV of AS patients faces a double load: valvular and arterial loads. As such, the presence of symptoms and occurrence of adverse events in AS should better correlate with calculating the global burden faced by the LV in addition to the transvalvular gradient and aortic valve area (AVA). The valvulo-arterial impedance (Zva) is a useful parameter providing an estimate of the global LV hemodynamic load that results from the summation of the valvular and vascular loads. In addition to calculating the global LV afterload, it is paramount to accurately estimate the stenosis severity. In clinical practice, the management of low-flow low-gradient (LF-LG) severe AS with preserved LV ejection fraction requires careful confirmation of stenosis severity. In addition to the Zva, the dimensionless index (DI) is a very useful parameter to express the size of the valvular effective area as a proportion of the cross-section area of the left ventricular outlet tract time-velocity integral (LVOT-VTI) to that of the aortic valve jet (dimensionless velocity ratio). The DI is calculated by a ratio of the sub-valvular velocity obtained by pulsed-wave Doppler (LVOT-VTI) divided by the maximum velocity obtained by continuous-wave Doppler across the aortic valve (AV-VTI). In contrast to AVA measurement, the DI does not require the calculation of LVOT cross-sectional area, a major cause of erroneous assessment and underestimation of AVA. Hence, among patients with LG severe AS and preserved LV ejection fraction, calculation of DI in routine echocardiographic practice may be useful to identify a subgroup of patients at higher risk of death who may derive benefit from aortic valve replacement. This article aims to elucidate the Zva and DI in different clinical situations, correlate with the standard indexes of AS severity, LV geometry, and function, and thus prove to improve risk stratification and clinical decision making in patients with severe AS.